Group decision-making within capital investment: a Fuzzy Analytic Hierarchy Process approach with developments. (1st December 2008) - Tang, Yu-Cheng; Beynon, Malcolm J.
In this study, a Fuzzy Analytic Hierarchy Process (FAHP) of a car hire purchasing problem is undertaken, with a group of decision makers involved in the judgements made. Developments on an existing FAHP method are exposited, including the sensitivity of the results when there is variation in the degree of fuzziness associated with the decisions made. The results presented further the understanding of the degree of fuzziness employed in the analysis, which directly attempts to model the inherent uncertainty, and incompleteness, in the specific preference judgements made.